LGBTQ in Islam: Further Considerations on Nature and Nurture Theory, Radical Feminism, and HIV/AIDS - Abdullah Muslich Rizal Maulana; Alif Nur Fitriyani; Arum Setyowati; Jehan Khalidin Ismail Jawawi (MUWAZAH : jurnal kajian gender, 2022)
This paper aimed to acknowledge LGBTQ as a distinct discourse that emerged from the very foundation of Radical Feminism with specific reference to Nature and Nurture theory, HIV/AIDS, and Islamic theology. This study employed the discourse analysis method to accomplish this goal. It focused on its ideologically beneficial impact by examining power relations in an established narrative, how power relations shape a society or organisation's LGBTQ practices, and analysing its creative change and repetition of ideas and behaviours. Consequently, This research explored LGBTQ from a chronological history and dynamic perspective of Feminism, as well as how such changes reflect and drive societal development of gender equality from sole emancipation of human rights to a radical bodily expression. As an additional reason for addressing the growing difficulty posed by the LGBTQ movement, this research concluded by doing a more in-depth investigation of Islamic teachings concerning the shortcomings of LGBTQ activity with further suggestions regarding better strategies to deal with this challenge.